Using a low-cost robotic manipulator towards the study of over-sensored systems and state estimation - Moreira, João (2021)
In this paper it is described a low-cost robotic manipulator that was developed to be applied in the study of over-sensored systems and state estimation. The prototype was developed to be a teaching aid in advanced courses, such as a Robotics Doctoral Program, although it is also suitable to be applied in some other educational contexts, to support experiments, for graduate and undergraduate students. Its features and software implementation are described, as well as two possible approaches to the problem of estimating its pose, based on a wide variety of sensors use.